Penataan Ruang Kawasan Perdesaan Sebagai Jabaran Rencana Tata Ruang Wilayah Yang Berbasis Komunitas - Harun, Uton Rustan (Center for Research and Community Services ITB, 1997)
In the Second Long-range Development Era, the Rural Development in Indonesia still occupied important issue in development due to the geo-demographical distribution, economic structures as well as contribution to the peoples way of life. Rural Spatial Planning as mention in Spatial Planning Law (Undang-Undang no 24 tahun 1992 tentang Penataan Ruang) intends to integrated several rural areas in one planning unit development called Kawasan Pedesaan. This idea is not questionable from planning and administrative point of view’s, but not from the communities. There are some good experiences that local communities demonstrated the ability to plan and manage their environment better than outsiders. The rurl people persistence to the development, modernization and no trusted the spatial planning, caused by “in and out” their preferences. Spatial planning is not belong to them. These planners challanges in rural planning shooed be copped in the near future.